Pengaruh Risiko Likuiditas Dan Risiko Kredit Terhadap Kinerja Keuangan Perbankan Melalui Kualitas Aset - Yuliastuti, Ririn; Apriyanto, Gaguk; Sihwahjoeni, Sihwahjoeni (Jurnal Publikasi Ekonomi dan Akuntansi, 2026)
This study examines the mediating role of asset quality in the relationship between liquidity risk, credit risk and banking financial performance. Using panel data from 11 commercial banks listed on the Indonesia Stock Exchange during 2022-2024, this research employs path analysis and multiple linear regression. The findings reveal that liquidity risk (LDR) and credit risk (NPL) significantly influence asset quality (AQR), with credit risk showing a stronger effect (β=0.668, p<0.001). However, neither liquidity risk nor credit risk directly affects financial performance (ROA). Asset quality emerges as a full mediator, demonstrating a significant negative effect on ROA (β=-1.122, p<0.001). The indirect effects through asset quality are -0.0325 for liquidity risk and -0.7494 for credit risk. These results highlight that asset quality serves as a critical transmission mechanism, providing more comprehensive signals to investors than NPL or LDR alone. This study contributes to signaling theory and financial intermediation theory by demonstrating that the relationship between banking risks and profitability operates through complex mechanisms rather than direct pathways.